Profiling and Characterization of Small RNAs in the Liverwort, Marchantia polymorpha, Belonging to the First Diverged Land Plants. (19th November 2015) - Tsuzuki, Masayuki; Nishihama, Ryuichi; Ishizaki, Kimitsune; Kurihara, Yukio; Matsui, Minami; Bowman, John L.; Kohchi, Takayuki; Hamada, Takahiro; Watanabe, Yuichiro
Abstract : MicroRNAs (miRNAs) have important roles in gene regulation during plant development. Previous studies revealed that some miRNAs are highly shared by most land plants. Recently, the liverwort, Marchantia polymorpha, has been studied by molecular genetic approaches, and sequencing of its genome is currently underway. The expression pattern and the detailed functions of miRNAs during Marchantia development are unknown. Here, we profiled the small RNAs expressed in thalli, antheridiophores and archegoniophores of M. polymorpha using high-throughput RNA sequencing. We revealed that a limited number of miRNAs are shared between M. polymorpha and the moss, Physcomitrella patens, and that a number of miRNAs are M. polymorpha specific. Like other land plants, cognate target genes corresponding to conserved miRNAs could be found in the genome database and were experimentally confirmed to guide cleavage of target mRNAs. The results suggested that two genes in the SPL (SQUAMOSA PROMOTER BINDING-LIKE) transcription factor family, which are regulated by miR156 in most land plants, were instead targeted by two distinct miRNAs in M. polymorpha. In order to demonstrate the physiological roles of miRNAs in M. polymorpha, we constructed an miRNA ectopic expression system to establish overexpression transformants for conserved miRNAs, miR166 and miR319. Ectopic expression of these miRNAs induced abnormal development of the thallus and gemma cups, suggesting that balanced expression of miRNA/target mRNAs has a crucial role in developmental regulation in M. polymorpha. Profiling data on miRNA together with the ectopic expression system would provide new information on the liverwort small RNA world and evolutionary divergence/conservation of small RNA function among land plants.